A biomarker found in cadmium exposed residents of thailand by metabolome analysis - Dhitiwass Suvagandha (2018)
First, the urinary metabolic profiling by gas chromatography-mass spectrometry (GC-MS), was performed to compare ten cadmium (Cd) toxicosis cases from a Cd-polluted area in Mae Sot (Thailand) with gender-matched healthy controls. Orthogonal partial list square-discrimination analysis was used to identify new biomarker candidates in highly Cd exposed toxicosis cases with remarkable renal tubular dysfunction. The results of the first step of this study showed that urinary citrate was a negative marker and myo-inositol was a positive marker for Cd toxicosis in Thailand. In the second step, we measured urinary citrate in the residents (168 Cd-exposed subjects and 100 controls) and found significantly lower levels of urinary citrate and higher ratios of calcium/citrate and magnesium/citrate, which are risk factors for nephrolithiasis, in highly Cd-exposed residents. Additionally, this inverse association of urinary citrate with urinary Cd was observed after adjustment fo r age, smoking and renal tubular dysfunction, suggesting a direct effect of Cd on citrate metabolism. These results indicate that urinary citrate is a useful biomarker for the adverse health effects of Cd exposure in a Thai population with a high prevalence of nephrolithiasis. © 2014 by the authors; licensee MDPI, Basel, Switzerland.